Implementasi Terapi Guided Imagery Untuk Penurunan Skala Nyeri Post Sectio Caesarea Di Rumah Sakit TK.II Putri Hijau Medan - Aisyah Nurhidayah; Huwaina Af’idah; Erita Gustina (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Labor is the process of expelling the products of conception, namely the fetus and placenta, after reaching full term and being viable in the womb. There are two types of delivery: normal delivery and caesarean section (SC). Caesarean section (SC) is a surgical procedure performed through an incision in the uterine wall to deliver the fetus. Caesarean delivery is indicate in cases of cephalopelvic disproportion, breech or transverse fetal position, fetal weight exceeding 4,000 grams, or maternal health conditions that may endanger the mother and fetus. One of the common complications following caesarean delivery is pain. Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. An intervention that can be applied to reduce post SC pain is Guided Imagery Therapy. Guided imagery therapy is a non-pharmacological intervention aimed at reducing and controlling pain by creating pleasant and relacing thoughts, focusing on breathing, and visualizing positive scenarios. This study employed a descriptive case study design using the nursing process from assessment to evaluation. The study was conducted on two patients with moderate pain (pain scale 4-6) after SC at TK II Putri Hijau Hosiptal Medan. The results showed that after the application of guided imagery therapy for three days with a duration of 40 minutes per session, pain levels decreased to mild (pain scale 1-3). In ptient I, pain decreased from a score of 5 to 3, an in patient 2, from a score of 6 to 3. In conclusion, guided imagery therapy was successfully applied in reducing post -SC pain levels and can serve as a reference for further research on pain reduction following caesarean section.